2015
DOI: 10.1111/imb.12203
|View full text |Cite
|
Sign up to set email alerts
|

Alternative migratory locust phenotypes are associated with differences in the expression of genes encoding the methylation machinery

Abstract: Despite the importance of locust density-dependent polyphenism as a model system for understanding phenotypic plasticity, there is still much to be learnt about its underlying molecular control. Here we describe the first investigation into the expression of genes encoding the DNA methylation machinery in the migratory locust (Locusta migratoria). We show that the alternative solitarious and gregarious phenotypic states induced by different locust rearing densities are associated with significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 69 publications
(106 reference statements)
1
16
0
Order By: Relevance
“…Our results, when coupled with those of prior investigations of arthropod Dnmt expression (Zwier et al, 2012;Yang et al, 2014;Mitsudome et al, 2015;Zhang et al, 2015;Robinson et al, 2016), reveal several commonalities among diverse arthropod taxa. In particular, extensive patterning of DNA methylation, as inferred by elevated Dnmt expression, apparently occurs in germ cells and embryos (Table 2).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results, when coupled with those of prior investigations of arthropod Dnmt expression (Zwier et al, 2012;Yang et al, 2014;Mitsudome et al, 2015;Zhang et al, 2015;Robinson et al, 2016), reveal several commonalities among diverse arthropod taxa. In particular, extensive patterning of DNA methylation, as inferred by elevated Dnmt expression, apparently occurs in germ cells and embryos (Table 2).…”
Section: Discussionsupporting
confidence: 79%
“…This suggests that DNMT1 functions primarily as a maintenance methyltransferase in B. mori, despite a putative secondary role in de novo methylation. Zwier et al (2012) Migratory locust, Locusta migratoria DNMT1 expression elevated in ovaries and testes relative to embryos and heads Robinson et al (2016) Brown planthopper, Nilaparvata lugens DNMT3 expression elevated in gravid females relative to other stages and males Zhang et al (2015) Two-spotted spider mite, Tetranychus urticae DNMT3 expression elevated in embryos and adult males relative to other stages; in situ hybridization consistent with elevated expression in ovaries and testes relative to other tissues Yang et al (2014) Our expression results in S. invicta are consistent with the presumed de novo function of DNMT3 and maintenance function of DNMT1. In particular, Dnmt3 was most highly expressed during embryonic development in S. invicta (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation in animals is accomplished by enzymes known as DNMTs, and recent studies have shown that DNMTs is associated with embryonic development in insect, such as S. invicta (Kay, Skowronski, & Hunt, ), Nasonia vitripennis (Zwier, Verhulst, Zwahlen, Beukeboom, & Zande, ), Locusta migratoria (Robinson et al, ), Nilaparvata lugens (Zhang et al, ), Tetranychus urticae (Yang, Guo, Xu, Sun, & Hong, ) and D. melanogaster (Lyko, Whittaker, Orr‐Weaver, & Jaenisch, ). Our results showed that the expression of BmDnmt1 and BmDnmt2 was higher in embryo than in other developmental stages (Figure ), and the expression was highest at the stage of 24 hr after oviposition (Figure ), which is the germ‐band formation stage of silkworm embryos (Ueno, Nagata & Suzuki, ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have identified gene sequences in L. migratoria that encode DNA methyltransferases (DNMT), a family of enzymes that catalyse the DNA methylation reaction (Robinson et al, ). These DNMTs are differentially expressed between the solitary and gregarious phases in both L. migratoria (Robinson et al, ) and S. gregaria (Boerjan et al, ), suggesting that differences in early environment lead to differences in the methylation control machinery. Such differences in DNMT expression can lead to changes in the epigenome, which in turn can alter gene expression and regulate developmental plasticity.…”
Section: Empirical Evidence Of Epigenetic Signallingmentioning
confidence: 99%
“…Such differences in DNMT expression can lead to changes in the epigenome, which in turn can alter gene expression and regulate developmental plasticity. Indeed, desert and migratory locusts have relatively high levels of DNA methylation compared to many other invertebrates (Falckenhayn et al, ), and differential methylation has been identified in over 90 genes and non‐coding transposable elements associated with adult phenotypes that reflect early‐life crowding conditions (Wang et al, ; Robinson et al, ). The dramatic differences in behaviour and morphology of locusts due to crowding conditions, despite the identical nucleotide sequence in their DNA, provides a compelling example of how epigenetic signals encoded early in life may alter adult phenotypes.…”
Section: Empirical Evidence Of Epigenetic Signallingmentioning
confidence: 99%